Abundance and antimicrobial susceptibility of Shigella spp. isolated from aquatic environments in Banda Aceh, Indonesia - YUNI ZAHARA; SUHARTONO SUHARTONO; NURLIANA NURLIANA (Society for Indonesian Biodiversity, 2022)
Abstract. Zahara Y, Suhartono S, Nirliana N. 2022. Abundance and antimicrobial susceptibility of Shigella spp. isolated from aquatic environments in Banda Aceh, Indonesia. Biodiversitas 23: 6420-6427. Accumulating pathogenic bacteria in aquatic systems increases waterborne infections, including shigellosis. The infection is causatively associated with Shigella spp. within the water system. This study aimed to isolate and determine the abundance of Shigella spp. collected from three rivers in Banda Aceh, Indonesia, namely Krueng Lamnyong, Krueng Aceh, and Krueng Neng water, and their antibiotic susceptibility. The bacterial enumeration was conducted using the MPN method followed by bacterial isolation using XLD and SSA selective media, whereas antibiotic susceptibility was evaluated using the standards of CLSI. Results showed that there was no significant difference (p=0.059) in the bacterial abundance among rivers i.e., 4.67 MPN/mL in Krueng Lamnyong, 27.33 MPN/mL in Krueng Aceh, and 18.33 MPN/mL in Krueng Neng. In total, 19 isolates of Shigella spp. were isolated, of which four isolates were from Krueng Lamnyong, nine isolates from Krueng Aceh, and six isolates from Krueng Neng. Antibiotic susceptibility test showed that the isolates had resistance to tetracycline, penicillin, and nalidixic acid. More than half of the isolates were resistant to more than five antibiotic classes. The study indicates that rivers are the main reservoir for the transmission of pathogenic bacteria in aquatic systems and some efforts are needed to reduce potential health risks and ensure water quality in aquatic systems.